Unsymmetrical Spatial Coding Algorithms for Overlay Cognitive Radio Network - Lan, Pengpeng; Yang, Xiao; Wang, Dong; Moon Ho Lee (5th IET International Conference on Wireless, Mobile and Multimedia Networks (ICWMMN 2013), 2013)
In this paper, the overlay cognitive radio (CR) network is considered. We proposed unsymmetrical spatial coding algorithms to cannel the interference between primary users (PUs) network and CR network. In the uplink of the overlay CR network, PUs and CUs are of one antenna, and need not to precode their transmitting signals, and primary base station (PBS) and cognitive base station (CBS) with two antennas can separate the received hybrid signals by using the proposed decoding algorithm. In the downlink, PBS and CBS need to joint precoding, and PUs and CUs need to joint decoding. The BER simulation results of the uplink and downlink are provided to verify the efficiency of the proposed spatial coding algorithms.